Comparative transcriptomics provides insight into the molecular basis of species diversification of section Trigonopedia (Cypripedium) on the Qinghai-Tibetan Plateau - Guo, Yan-Yan (Sci Rep, 2018)
Deceptive pollination is key to the species richness of Orchidaceae. However, the genetic basis of species diversification is still under study. Section Trigonopedia is a monophyletic clade of genus Cypripedium distributed in the southwest of China. The species of this section are pollinated by different flies. Pollinator differentiation makes section Trigonopedia an ideal group for studying the genetic basis underlying species diversification. Here, we sequenced the transcriptomes of eight species of the genus Cypripedium, including six co-flowering species of section Trigonopedia and two species outside this section as an outgroup. We reconstructed the phylogeny of the section with the combined 1572 single-copy genes extracted from the eight species and produced a highly resolved tree of the section. Furthermore, we combined substitution rate estimation and differential expression analysis to identify candidate genes, including genes related to floral scent synthesis and environmental adaptation, involved in species differentiation. Field investigations showed that these species have adapted to different habitats. We propose that the species diversification in this section is initiated by floral scent differentiation, followed by habitat differentiation, finally leading to speciation. This study sheds novel light on the diversification of closely related orchid species in the Qinghai-Tibetan region.